Letter (copy) : Conference, 11th April - McDonald, Florence
032-0078-001 Secretary's. FEM/FP/334 4th April, 1939. Mr. W. Schevenels, International Federation of Trade Unions, 9, Avenue D'Orsay, Paris, VIIe, France. Dear Mr. Schevenels, Conference, 11th April. Thank you for your letter of the 1st April, asking Sir Walter to attend the Conference of International Trade Secretariats to be held on the 11th April, with a view to the examination of the problem of co-ordinating relief action for the Spanish refugees within the I.F.T.U. I regret that Sir Walter will not be able to attend. He is arriving back in England during the Easter holidays, but there are many big problems awaiting him here. We would be very grateful if you would let us have a detailed report of the Conference in due course. Yours fraternally, Private Secretary. 292/946/32/78